2001
DOI: 10.1016/s0308-0161(01)00108-9
|View full text |Cite
|
Sign up to set email alerts
|

A unified European approach to high temperature defect assessment code and its incorporation in a knowledge base system

Abstract: The background to high temperature defect assessment methodologies is investigated and similarities and differences are highlighted. It is clear that Europe is a leader in this developing field. Comparison of the existing European high temperature life assessment codes [1][2][3][4][5][6][7][8][9] lead to the conclusion that crack initiation is dealt with in different ways by the codes whereas creep and creep/fatigue crack growth are considered using the same models for analysis. At the same time whilst increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In this case, the predictions from R5 were in good agreement with experimental flaw propagation. A comprehensive comparison of existing European high-temperature codes (including R5) is presented by Nikbin [15]. Differences and sensitivity to specific analysis techniques is provided and a methodology based on deterministic and probabilistic techniques is suggested.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this case, the predictions from R5 were in good agreement with experimental flaw propagation. A comprehensive comparison of existing European high-temperature codes (including R5) is presented by Nikbin [15]. Differences and sensitivity to specific analysis techniques is provided and a methodology based on deterministic and probabilistic techniques is suggested.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Usually at short times the stress intensity factor K, or the elastic-plastic parameter J, is employed to describe the stress and strain distributions at a crack tip whereas at long times, when steady state conditions have been reached, the creep fracture mechanics term C* is used. 8,[16][17][18][19][20] During the intervening stage damage formation and stress redistribution is occurring at the crack tip. The parameters are validated by the right usage of parameters to describe creep brittle and creep ductile crack growth.…”
Section: Parameters For Analysing Creep/fatigue Crackingmentioning
confidence: 99%
“…[16][17][18][19][20] The derivation for C* which is analogous to J is well documented 16,17 and will not be detailed in this paper. Once a steady state distribution of stress and creep damage has been developed ahead of a crack tip, it is usually found that creep crack growth rate can be described by an expression of form [16][17][18][19][20] …”
Section: Steady State Ccg Analysismentioning
confidence: 99%
“…To assess the compliance to safety conditions, in the recent past, the verification of process plants has been improved through the application of KB technologies. In two works [4, 5], both originated from the research carried out in the European project HIDA [6], the authors apply KB technologies to the assessment of cracks in plant components, underlining the benefits deriving from the incorporation of defect checking code into a KB system. In the project TTF 2,6 which is supported by the European Pressure Equipment Research Council and is aimed at promoting the use of High Strength Steels, the integration of a new analysis method with appropriate material data into a KB system is proposed.…”
Section: Background and Related Workmentioning
confidence: 99%